Analisis Aliran Material Limbah Domestik di Pembangkit Listrik Tenaga Batubara - Wicaksono, Aris Dwi; Bagastyo, Arseto Yekti (Jurnal Serambi Engineering, 2025)
This study evaluates the zero waste strategy for managing domestic solid waste within the operational environment of a large-scale coal-fired power plant (CFPP) in East Java. The Material Flow Analysis (MFA) method, which uses STAN 2.7.101 software, was employed to map waste flows and evaluate the potential for recovery. Data were collected through field observations, representative sampling and laboratory analysis, including proximate and ultimate testing. The results show that organic waste, such as leaves, food scraps and fruit peels, accounted for over 85 per cent of total waste generation. With recovery factors (RF) exceeding 70 per cent, this supports composting and maggot-based biodegradation. In contrast, inorganic waste, such as plastics and used pipes, had lower RF values ranging from 15 to 45 per cent. MFA modelling estimated that 25–30% of the total waste would remain as residue to be sent to landfill. This study emphasises the importance of reducing and recovering waste upstream to minimise final disposal. The study's originality lies in its systemic focus on domestic waste within an energy industry infrastructure, using MFA and RF as a robust basis for adaptive, sustainable waste management strategies.